Isolation of pigment-producing strain of Staphylococcus kloosii from the respiratory tree of Holothuria (Mertensiothuria) leucospilota (Brandt, 1835) from Malaysian waters - Kamarudin, Kamarul Rahim; Ngah, Nurziana; Tengku Abdul Hamid, Tengku Haziyamin; Darnis, Deny Susanti (Penerbit Universiti Sains Malaysia, 2013)
Staphylococcus kloosii, an orange pigment-producing bacterium, was isolated from the respiratory tree of Holothuria (Mertensiothuria) leucospilota (Brandt 1835) from Teluk Nipah, Pangkor Island, Perak, Malaysia. This report is the first documentation of this Gram-positive strain, referred to as Strain 68 in Malaysia. A partial 16S ribosomal RNA gene sequence of the mesophilic strain has been registered with GenBank (National Center for Biotechnology Information, US National Library of Medicine) with accession number JX102547. Phylogenetic analysis using the neighbour-joining method further supported the identification of Strain 68 as S. kloosii. The circular strain produced orange pigments on tryptone glucose yeast extract agar (TGYEA) and in nutrient broth (NB) at approximately pH 7. The visible spectra of ethanolic and methanolic pigment extracts of the bacterial strain were considered identical with λmax at 426, 447 and 475 nm and λmax at 426, 445 and 473 nm, respectively. Both visible spectra resemble the visible spectra of lutein, which is a commercial carotenoid; however, further analyses are required to confirm the identity of this pigment. The methanolic extracts of the intracellular pigments comprised at least three pigment compounds: an orange pigment compound (major compound), a yellow pigment compound (the least polar) and a pink pigment compound (the most polar). These findings are the first documentation of the pigment composition of S. kloosii as no such record could be found to date.